A PROPOLIS AS A HEALING AGENT FOR PULP INJURIES - Mirza Aryanto; Siti Nur Khairunnisa Alala (Universitas prof. Dr. Moestopo (Beragama), 2021)
As one of the natural resin materials produced by bees, propolis has been used as a traditional medicine for various diseases because of its biological and pharmacological activities. The purpose of this study was to analyze the potential of propolis as a healing agent for pulp injuries. A total of 35 journals from PubMed, Ebsco, ResearchGate, Wiley Online Library, and other international journal databases were analyzed. Propolis is very rich in active components such as flavonoids that have biological functions such as anti-inflammatory, antibacterial, antifungal and antioxidant which can act as a potential healing agent